Treatment of metastatic castration-resistant prostate cancer: review of current evidence and synthesis of expert opinions on radioligand therapy - Poon, Darren M. C.; Cheung, William S. K.; Chiu, Peter K. F.; Chung, Daniel H. S.; Kung, John B. T.; Lam, Daisy C. M.; Leung, Angus K. C.; Ng, Anthony C. F.; O’Sullivan, Joe M.; Teoh, Jeremy Y. C.; Wu, Philip Y.; Wu, Sam K. K.; et al. (Frontiers in Oncology, 2025)
BackgroundDespite the boom in the development of cancer management in the last decade, most patients with metastatic prostate cancer (PCa) eventually progress to metastatic castration-resistant PCa (mCRPC) and often require multiple lines of treatment. The treatment landscape of mCRPC has evolved rapidly in recent years, introducing various types of systemic therapies, including taxane-based chemotherapy, androgen receptor pathway inhibitors, bone-targeted radionuclides (e.g., radium-223), immune checkpoint inhibitors, poly(adenosine diphosphate [ADP]-ribose) polymerase (PARP) inhibitors, and radioligand therapies (RLTs) [e.g., a prostate-specific membrane antigen (PSMA) ligand labelled with 177Lu].MethodsTo help clinicians navigate the increasingly complex treatment landscape of mCRPC, this article reviews the evidence on different therapeutic regimens from pivotal trials. In addition, it reports on the results of a questionnaire developed and distributed by the Hong Kong Society of Uro-Oncology (HKSUO), with the aim of collecting the perspectives of specialists experienced in the treatment of advanced PCa in Hong Kong with regard to the clinical application of RLT, primarily [177Lu]Lu-PSMA-617/analogue therapy.ResultsA total of 43 questionnaire respondents (including clinical oncologists, urologists, nuclear medicine specialists, and medical oncologists) voted on 27 consensus questions divided into eight sections. Consensus or strong consensus (correspondingly ≥75% or ≥90% acceptance for an answer option) was reached for 10 questions. Subsequently, a panel of 13 local and overseas experts coordinated by the HKSUO discussed the voting results and provided further insights into certain questions.ConclusionThe literature review, the voting results of the questionnaire, and the expert opinions are expected to facilitate better understanding of recent therapeutic advancements and the role of novel RLTs in the treatment of mCRPC among clinicians.